Model parameter sensitivity and benchmarking of the explicit dynamic solver of LS-DYNA for structural analysis in case of fire - Rackauskaite,E; Kotsovinos,P; Rein,G (Fire Safety Journal, 2017)
Due to the complex nature of structural response in fire, computational tools are often necessary for the safe design of structures under fire conditions. In recent years, use of the finite element code LS-DYNA has grown considerably in research and industry for structural fire analysis, but there is no benchmarking of the code available in the fire science literature for such applications. Moreover, due to the quasi-static nature of structural response in fire, the majority of the computational structural fire studies in the literature are based on the use of static solvers. Thus, this paper aims at benchmarking the explicit dynamic solver of LS-DYNA for structural fire analysis against other static numerical codes and experiments. A parameter sensitivity study is carried out to study the effects of various numerical parameters on the convergence to quasi-static solutions. Four canonical problems that encompass a range of thermal and mechanical behaviours in fire are simulated. In addition, two different modelling approaches of composite action between the concrete slab and the steel beams are investigated. In general, the results confirm that when numerical parameters are carefully considered such as to not induce excessive inertia forces in the system, explicit dynamic analyses using LS-DYNA provide good predictions of the key variables of structural response during fire.